Concepts and measurement of vulnerability to poverty and other issues: A review of literature - Tomoki Fujii (Asian Development Bank Institute (ADBI), 2016)
This paper reviews the growing body of literature on vulnerability. We first provide a survey of existing studies on the concepts and measurements of vulnerability to poverty by classifying them into welfarist, expected poverty, and axiomatic approaches. We then review a number of empirical studies on vulnerability to poverty in Asia and elsewhere. This review shows that poverty and vulnerability are related, but different, and that key determinants of vulnerability often include education and location. We also briefly review other areas of vulnerability analysis such as vulnerability to climate change and offer various policy implications arising from vulnerability analysis.
Keywords: I32; O10; 330; poverty; vulnerability